Opinions of Foreign Scholars on Pashto Language - Pohanyar Nasratullah Nasrat; Pohanyar Hejratullah Mobashir (Randwick International of Education and Linguistics Science Journal, 2022)
Pashto has always attracted the attention of scholars from the language of the eastern group of Aryan language throughout history. This will be a special structure of Pashto language so scholars have given different views on this language and its speakers. There may be some quotations in this commentary. self –research has also been done that confirms the authenticity of the language in the opinion of most researchers and writhers. The descriptive and analytical method used in this research. To address the issue the goal is to get those ideas out first which has been given by foreign scholars on Pashto language not only local scholars but also many western writhers have done research on Pashto language and gave his views on it. Which in turn is appreciated. Because it paved the way for the introduction of Pashto language and its origin and roots and he introduced the language to the world outside the region.